Translation system from Tunisian Dialect to Modern Standard Arabic. (16th December 2021) - Torjmen, Roua; Haddar, Kais
Summary: Nowadays, Tunisian Dialect (TD) is widely used in social media such as Facebook and Twitter to communicate and express opinions. However, the absence of a TD translator prevents comprehension and communication for non‐Tunisian users. Thus, Tunisian translator becomes an important task to overcome these problems. In this article, our main objective is to create a translator from TD to Modern Standard Arabic (MSA). In this context, we are carrying out an in‐depth linguistic study in order to better choose the translation rules which are applicable on the TD sentences. This study guarantees the best quality to obtain MSA sentences. Indeed, our proposed method is based on a linguistic approach. In addition, the method consists of the elaboration of a set of dictionaries and the construction of inflectional, morphological, and syntactic grammars using finite‐state transducers. Then, our method is implemented and tested with new technologies provided by the NooJ linguistic platform. To evaluate our constructed tool, we apply it to two different test corpora containing more than 15, 000 words. The obtained results are promising and do highlight our proposed method.